Climate-Resilient Healthcare Facilities: Time for a National Policy in India - Pandve, Harshal T; Giri, Purushottam (Indian Journal of Community Health, 2025)
Climate change is no longer a distant threat climate change has emerged as one of the most devastating environmental threat. Climate change is increasingly impacting public health in India, leading to increased prevalence of heat-related illnesses, vector-borne diseases, and other climate-sensitive conditions. India needs a national policy for climate-resilient healthcare facilities to address the growing threat of climate change on public health. Various studies have demonstrated that there is an urgent need to address climate related health hazards in the medical education.[1] Climate change is also an immediate and growing risk to public health infrastructure in India. Numerus incidents shown that India's healthcare system is increasingly vulnerable to the consequences of climate change, including extreme weather events, rising temperatures, and water scarcity. These environmental shifts threaten the delivery of health services, damage critical infrastructure, and compromise patient safety. Despite this, the concept of climate-resilient healthcare remains largely under-addressed in national health policies. This editorial calls for the urgent development and implementation of a national policy in India to build climate-resilient and low-carbon healthcare facilities. Drawing from global examples and aligning with India's existing public health and environmental frameworks, such a policy would be a significant step toward safeguarding health systems against future climate shocks. The growing frequency of extreme weather events—floods, heatwaves, cyclones, and droughts—poses a dual threat: to public health and the healthcare facilities themselves. Healthcare institutions, meant to be sanctuaries during crises, are increasingly becoming victims of climate-related disasters.